1996
DOI: 10.1002/(sici)1099-1026(199607)11:4<223::aid-ffj579>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Constituents from the Fruits of Four Edible Sapindaceae: Rambutan (Nephelium lappaceum L.), Pulasan (N. ramboutan-ake (Labill.) Leenh.), Longan (Dimocarpus longan Lour.), and Mata Kucing (D. longan ssp.malesianus Leenh.)

Abstract: The volatile constituents of fruits from two Nephelium and two Dimocarpus species were analysed by capillary GC and GC-MS following isolation by vacuum distillation. In total, 48,39,61 and 44 constituents were identified in rambutan (N. lappaceum L.), pulasan ( N . ramboutan-ake (Labill.) Leenh.), longan (D. longan Lour.) and mata kucing (D. longan ssp. malesianus Leenh.), respectively. Among rambutan volatiles, aliphatic alcohols (49.0%), sesquiterpenoids (20.5%) and carbonyl compounds (19.5%) predominated, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 0 publications
0
5
1
Order By: Relevance
“…A total of 47 flavor compounds were detected using chromatography analysis. According to Wong et al. (1996), a total of 61 volatiles were identified by GC‐MS following vacuum distillation, and ethyl acetate and ( E )‐β‐ocimene were the two most abundant components.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 47 flavor compounds were detected using chromatography analysis. According to Wong et al. (1996), a total of 61 volatiles were identified by GC‐MS following vacuum distillation, and ethyl acetate and ( E )‐β‐ocimene were the two most abundant components.…”
Section: Resultsmentioning
confidence: 99%
“…Laohakunjit et al 39 reported that the most abundant volatile compounds in rambutan Nephelium lappaceum L. var Rong-rien fruit were isocitonellol, 3-hydroxy-2-butanone, pentanal, and 4-tridecyl valerate. Wong et al 40 reported that the major components among rambutan volatiles were aliphatic alcohols 49.0 , sesquiterpenoids 20. 5 and carbonyl compounds 19.5 predominated, 2-methylbut-3-en-2-ol 21.9…”
Section: Aroma Pro Lementioning
confidence: 99%
“…malesianus Leenh. ), respectively (Wong, Wong, Loi, & Lim, 1996). Among rambutan volatiles, aliphatic alcohols (49.0%), sesquiterpenoids (20.5%) and carbonyl compounds (19.5%) predominated, 2-methylbut-3-en-ol (21.9%) and β-caryophyllene (10.4%), constituting the major components.…”
Section: Comparison Between Different Exotic Fruitsmentioning
confidence: 99%